Identification of QTL associated with the symbiosis of Bradyrhizobium japonicum; B. elkanii and soybean - Santos, Maria Aparecida dos; Nicolás, Marisa Fabiana; Hungria, Mariangela (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to identify QTL (Quantitative Trait Loci) related to biological nitrogen fixation (BNF) using microsatellites (SSR) markers, in an F2:7 population of soybean (Glycine max) cultivars with contrasting capacities of BNF, Bossier (high) and Embrapa 20 (medium). 16 markers located in six linkage groups have been mapped, covering about 5% of the genome (151.6 cM). The regression analysis identified 12 significant associations in four linkage groups (B1, C2, D1b and H): three for shoot dry weight, four for nodule number, four for nodule weight and three for the medium value of nodule weight. All QTL had minor effects. However, seven QTL were confirmed in both populations, indicating that they might be effective in increasing BNF in soybean breeding programs.